2020
DOI: 10.1093/sleep/zsaa117
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between machine-learning-derived sleep parameters and behavior problems in 3- and 5-year-old children: results from the CHILD Cohort study

Abstract: Study Objectives Machine learning (ML) may provide insights into the underlying sleep stages of accelerometer-assessed sleep duration. We examined associations between ML-sleep patterns and behavior problems among preschool children. Methods Children from the CHILD Cohort Edmonton site with actigraphy and behavior data at 3-years (n = 330) and 5-years (n = 304) were included. Parent-reported behavior problems were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Despite evidence using device-assessed sleep behaviors is limited, the few previous studies observed that device-estimated sleep duration was related to behavioral J o u r n a l P r e -p r o o f functioning in children [15][16][17]40]. However, our findings are in agreement with those from Hammam et al [14], supporting that total sleep duration was not a predictor of behaviors problems among preschool children. Guerlich et al [17] found that longer device-assessed sleep duration was not associated with externalizing problems in 8-yearold children.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite evidence using device-assessed sleep behaviors is limited, the few previous studies observed that device-estimated sleep duration was related to behavioral J o u r n a l P r e -p r o o f functioning in children [15][16][17]40]. However, our findings are in agreement with those from Hammam et al [14], supporting that total sleep duration was not a predictor of behaviors problems among preschool children. Guerlich et al [17] found that longer device-assessed sleep duration was not associated with externalizing problems in 8-yearold children.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Device-assessed sleep duration has shown inconsistent associations with behavioral problems in children [14][15][16][17]. For example, longer sleep duration was associated with lower risk of internalizing, but not externalizing problems in 8-year-old children [17].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…These assumptions are essential in a rigorous IRT analysis. Given the emerging interest among empirical studies in reporting behavior problems at these two subscale levels (e.g., Hammam, et al, 2020; Quiñones-Camacho, et al, 2021; Rodrigues et al, 2022; Steenhoff et al, 2021), a more comprehensive IRT study on the externalizing and internalizing subscale scores is needed, To our knowledge, this is the first study applying IRT analysis to examine the psychometric properties of the CBCL/1½ – 5 among preschool children, particularly those who are from low-income population.…”
Section: Introductionmentioning
confidence: 99%